Improving the numerical convergence of viscous-plastic sea ice models with the Jacobian-free Newton-Krylov method - Lemieux, Jean-Francois; Tremblay, Bruno; Sedláček, Jan; Tupper, Paul; Thomas, Stephen; Huard, David; Auclair, Jean-Pierre (Journal of Computational Physics, 2010)
ISSN:0021-9991 ISSN:1090-2716